The Ability of Porcine Reproductive and Respiratory Syndrome Virus Isolates to Induce Broadly Reactive Neutralizing Antibodies Correlates With In Vivo Protection - Martínez-Lobo, Francisco Javier; Díez-Fuertes, Francisco; Simarro, Isabel; Castro, José M.; Prieto, Cinta (Frontiers in Immunology, 2021)
Porcine reproductive and respiratory syndrome (PRRS) is considered one of the most relevant diseases of swine. The condition is caused by PRRS virus (PRRSV), an extremely variable virus of the Arteriviridae family. Its heterogeneity can be responsible, at least partially, of the poor cross-protection observed between PRRSV isolates. Neutralizing antibodies (NAs), known to play a role in protection, usually poorly recognize heterologous PRRSV isolates, indicating that most NAs are strain-specific. However, some pigs develop broadly-reactive NAs able to recognize a wide range of heterologous isolates. The aim of this study was to determine whether PRRSV isolates that induce broadly reactive NAs as determined in vitro are able to confer a better protection in vivo. For this purpose two in vivo experiments were performed. In the first one 40 pigs were immunized with a PRRSV-1 isolate known to induce broadly-reactive NAs and 24 additional pigs were used as controls. On day 70 after immunization the pigs were divided into 8 groups composed by 5 immunized and 3 control pigs and exposed to one of the eight different heterologous PRRSV isolates used for challenge. In the second experiment the same experimental design was followed but the pigs were immunized with a PRRSV-1 isolate known to generate mostly strain-specific NAs. Virological parameters, specifically viremia and the presence of challenge virus in tonsils, were used to determine protection. In the first experiment, sterilizing immunity was obtained in three groups, prevention of viremia was observed in two additional groups, although the challenge virus was detected occasionally in the tonsils of immunized pigs, and partial protection, understood as a reduction in the frequency of viremia compared to controls, was recorded in the remaining three groups. On the contrary, only partial protection was observed in all groups in the second experiment. The results obtained in this study confirm that PRRSV-1 isolates differ in their ability to induce cross-reactive NAs and, although other components of the immune response might have contributed to protection, pigs with cross-reactive NAs at the time of challenge exhibited better protection, indicating that broadly-reactive NAs might play a role in protection against heterologous reinfections.